Total edge irregularity strength of some families of graphs - Jeyanthi P.; Sudha A. (Utilitas Mathematica, 2018)
An edge irregular total labeling / : V U £ (1,2,3,...k) of a graph G = (Vt£) is a labeling of vertices and edges of G in such a way that for any two different edges uv and u'v' their weights f{u) + f{uv) + /(v) and f(u') + f(uW) + /(v') are distinct. The total edge irregularity strength tes{G) is defined as the minimum k for which the graph G has an edge irregular total A-labeling. In this paper, we study the total edge irregularity strength for tadpole T(n,t), n £ 3, / > 1, armed crown (CH C Pm), for n £ 3,m > I, split graph of cycle and split graph of a path. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.